Neurogenesis in the Dentate Gyrus of the Rat Following Electroconvulsive Shock Seizures - Scott, Brian W.; Wojtowicz, J.Martin; Burnham, W.McIntyre (Experimental neurology, 2000)
Electroconvulsive shock (ECS) seizures provide an animal model of electroconvulsive therapy (ECT) in humans. Recent evidence indicates that repeated ECS seizures can induce long-term structural and functional changes in the brain, similar to those found in other seizure models. We have examined the effects of ECS on neurogenesis in the dentate gyrus of the adult rat using bromodeoxyuridine (BrdU) immunohistochemistry, which identifies newly generated cells. Cells have also been labeled for neuronal nuclear protein (NeuN) to identify neurons. One month following eight ECS seizures, ECS-treated rats had approximately twice as many BrdU-positive cells as sham-treated controls. Eighty-eight percent of newly generated cells colabeled with NeuN in ECS-treated subjects, compared to 83% in sham-treated controls. These data suggest that there is a net increase in neurogenesis within the hippocampal dentate gyrus following ECS treatment. Similar increases have been reported following kindling and kainic acid- or pilocarpine-induced status epilepticus. Increased neurogenesis appears to be a general response to seizure activity and may play a role in the therapeutic effects of ECT.